Modeling of nutritional behavior and harvest profit margin in fattening pacu (Piaractus mesopotamicus) fed on balanced digestible protein contents and raised in an intensive recirculating aquaculture system - Khan, Kifayat Ullah [UNESP]; Gous, Robert Mervyn; Nascimento, Thiago Matias T. [UNESP]; Sakomura, Nilva Kazue [UNESP]; Mansano, Cleber Fernando M.; Queiroz, Daniel Monge A. [UNESP]; Rodrigues, Andressa Tellechea [UNESP]; Boaratti, André Zuffo [UNESP]; de Souza Romaneli, Rafael [UNESP]; Fernandes, João Batista K. [UNESP] (Elsevier, 2022)
Adjusting aquafeed to obtain sustainable growth and maximum profit margin of harvest is a worthy stride toward achieving the Sustainable Development Goals (SDGs) outlined by the United Nations. Therefore, this research aimed at modeling of nutritional behavior and harvest profit margin in fattening pacu (Piaractus mesopotamicus) fed on balanced digestible protein (BDP) contents and raised in an intensive recirculating aquaculture system (RAS). The feeding trial consisted of six treatments with three randomly arranged replicates (tanks) per treatment. A total of ten fattening pacus (490.60 ± 14.39 g, initial weight) were stocked per tank. Six experimental feeds containing the increasing contents (163, 201, 238, 272, 315, and 348 g kg-1 diet, dry matter) of BDP were manually fed to the fish for seven weeks three times a day until apparent satiation. The data obtained over the test diets were assessed through appropriate statistical procedures and mathematical models. Optimal levels of BDP were calculated for different nutritional and economic scenarios. Feed cost showed an ascending linear relationship with the BDP intake. Feed intake, feed efficiency, final body weight, weight gain, and specific growth rate (%) showed an inverted U-shaped quadratic behavior (P < 0.05). Feed conversion ratio showed a U-shaped quadratic behavior (P < 0.05). Protein efficiency ratio significantly (P < 0.05) decreased linearly in response to the increasing BDP contents. Final weights of the eviscerated and sliced fish showed an ascending linear behavior, but the overall effect was insignificant (P > 0.05) between the treatments. Whole body moisture and crude protein content increased (P < 0.05) linearly, while the whole body lipid content decreased (P < 0.05) linearly over the increasing BDP intake. Whole body ash content showed a U-shaped quadratic behavior (P < 0.05). The nutritionally optimal BDP content corresponding to the maximum gain in body weight of fattening pacu was calculated as 292 g kg-1 diet (dry matter). To obtain sustainable growth and maximum profit margin of harvest when it will be sold in the form of whole-body, eviscerated, and sliced fish the economically functional BDP intakes were calculated as 249, 256, and 260 g kg-1 diet (dry matter), respectively. This research revealed that the optimal BDP intake greatly improve the nutritional performance of fattening pacu. Moreover, harvest profit margin and eventually the economically sustainable BDP intakes were found dependent on the way the fish harvest is marketed and the changes in total feed cost.
Keywords: Gross margin maximization; Intensive farming; Low-cost balanced feed; Sustainable development goals; Sustainable growth